A study on the relationship between Notch and TGF signal pathways in renal interstitial fibrosis - ZHANG Man; LI Jun (Linchuang shenzangbing zazhi)
Renal interstitial fibrosis is a necessary stage in the development of many chronic renal diseases. Signal pathways regulate the transcription of a variety of functional genes and participate in many important physiological and pathological processes. Signal pathways play an important role in the occurrence and development of renal interstitial fibrosis. Both TGF and Notch signaling pathways are involved in the occurrence and development of renal fibrosis. Intervention of TGF and Notch signaling pathways can delay the progression of renal interstitial fibrosis. It is shown that TGF signaling pathway and Notch signaling pathway not only play an independent role, but also interact with each other. Both of them not only regulate the activity of each signal pathway component, but also regulate the common downstream target genes and expression products, so as to regulate the occurrence and development of renal interstitial fibrosis. Therefore, further studies of the relationship between the two pathways may provide a new entry point for the study of anti-renal fibrosis.